Bem-estar dos animais não humanos e abates ritualísticos: liberdade religiosa e limite do bom-costume / Non-human animals well-being and ritual slaughter: religious freedom and good custom limit - Biscontini, Giorgio (Revista do Programa de Pós-Graduação em Direito, 2015)
This article defines the shape of legal balancing between animal well-being and religious freedom. With the development of human society and numerous areas of human knowledge and, thereafter, of Law itself, mainly the environmental one, it is perceived as essential to discuss the present need to defend the animal’s well-being. Thereby, it becomes mandatory to investigate the boundaries of religious freedom itself, besides the related national and community legal evolution, as an attempt to critically elucidate the tempestuous process of sentient beings reification. It is worth noting that, with technological progress, a significant massification of the food production process was allowed, which increased the reification process of the animals, seem as res, thing, before the capitalist system. Nowadays, however, the technological progress can already be thought as a mechanism tied to the guarantee of a better well-being for the animals. Therefore, it is questioned if previously stunning is needed or not to when it comes to animal slaughtering, in its own legal and moral limits, including the analysis of the applicable sanction.